School and territory: some feedback from the Self Evaluation Report - Rosanna Tammaro; Marika Calenda; Ciro Clemente De Falco; Concetta Ferrantino (Firenze University Press, 2017)
What is the relationship with the territory of high schools in the province of Salerno? Are there differences in the integration's levels with the territory on the basis of different territorial spheres? To what extent do schools feel able to involve families in the formative project? Do the socio-economic characteristics of the area affect the action of the school? Which differences can we observe at national and regional level? This article aims to provide some answers to these questions through a descriptive analysis of integration with the territory of high schools in the province of Salerno, starting with the topic of quality in school management and self-evaluation like an agent for improvement. Specifically, a documentary analysis is carried out on the schools Self-assessment reports, analyzing contents of the answers provided by the compiler's self-declaration.   Scuola e territorio: alcuni riscontri dal Rapporto di Autovalutazione Qual è il rapporto con il territorio delle scuole secondarie di secondo grado della provincia di Salerno? Ci sono delle differenze nei livelli di integrazione con il territorio in base ai diversi ambiti territoriali? In che misura le scuole si sentono in grado di coinvolgere le famiglie nel progetto formativo? Le caratteristiche socio-economiche del territorio influenzano l'azione della scuola? Che differenze è possibile riscontrare a livello nazionale e regionale? Il presente articolo intende fornire alcune risposte a tali domande attraverso un'analisi descrittiva dell'integrazione con il territorio degli Istituti Secondari Superiori della provincia di Salerno, partendo dal tema della qualità nella gestione della scuola e dell'autovalutazione come agente di miglioramento. Nello specifico viene effettuata un'analisi documentale sui Rapporti di autovalutazione delle scuole, analizzandone i contenuti, ossia le risposte fornite dalle autodichiarazioni dei redattori.